Entre sentidos e desafios: trajetórias laborais de transexuais da cidade de Fortaleza, Ceará - Lopez, Valeria Yanela Pablo (2020)
This investigative study aims to identify and analyze the challenges and meanings attributed to work by transsexuals, through the understanding of their work paths in the city of Fortaleza, Ceará, enticing that the research on sexual and gender diversity has revealed, over time, traces of a heteronormative society that rejects and discriminates against people who do not fit in the culturally imposed standards. Therefore, we highlight the work perspective for understanding work as an activity that fulfills an important psychosocial function in life. Thus, the investigation was organized in two stages. At first, we carried out a bibliographical survey on transsexuality and its relationship with the working world, aiming to achieve a theoretical overview that serves as a basis for the reflections. In a second stage, we conducted interviews with two transsexuals living in the city of Fortaleza, Ceará. The method used in the second stage of the investigation was The Life History based on the approach of Clinical Psychosociology, in order to apprehend the articulations between the individual and the collective history. This study revealed that transsexuals still front numerous obstacles to face the labor market and to be accepted into it, difficulties that often start long before these people apply for a job, leading them to create many survival strategies. However, work remains a central component in the lives of these people, attributing meanings and developing important psychosocial functions in their experiences.